Effectiveness of STEAM Coding (Animation and Game) Application Through Web Scratch on 4C Skills - Khusnul Qomatfian, Livvia; Ngazizah, Nur; Rizkia Pangestika, Rintis (Education, Science, and Technology International Conference, 2024)
This study aims to determine the effectiveness of the application of digital coding media from several STEAM disciplines (Science, Technology, Engineering, Art, and Math) based on scratch in the form of animated coding and games on 4C skills (Critical Thinking, Creative, Collaborative, and Communication). Researchers examined this because the school under study already has a coding curriculum whose application has not been seen for its effectiveness. In addition, coding learning there has not used the STEAM approach learning method. Whereas implementing coding learning with the STEAM method can foster, even develop computer skills and 4C students. This research was conducted at English Program Phrathom (Elementary) Sangkhom Islam Wittaya School, Sadao, Songkhla, Thailand with a total of 32 students using the total sample technique. The type of research used is experimental quantitative research with comparative and descriptive statistics. The research approach used a quasi-experimental posttest only design. Data collection used observation, interview, and documentation techniques. The data obtained in this study is ordinal data, so the data analysis technique is Nonparametric Inferential Design using paired sample t test from the application of animated coding and STEAM games and descriptive statistical tests to determine the effectiveness of each learner’s 4C skills. The results of this study show that 1. There is a significant difference in the application of STEAM coding seen from the correlation of the two of 0.77 and a significance number of 0.00 and the mean application of STEAM Animation coding of 91.71 is more effective than the application of digital media coding STEAM game of 84.06. 2. Knowing the 4C skills of students in the application of animation and games through the average value in each section, so it can be seen that in the application of coding STEAM animation 4C skills are honed starting from Critical Thinking of 22.03, creative of 23.28, Communication of 22.96, and Collaboration of 23.43 and the application of coding STEAM games 4C skills are honed starting from Critical thinking of 20.62, Creative of 21.87, Communication of 20.31, and Collaboration of 21.25.